Risk factors for bleeding, including platelet count threshold, in newly diagnosed immune thrombocytopenia adults. (12th August 2018) - Piel‐Julian, M.‐L.; Mahévas, M.; Germain, J.; Languille, L.; Comont, T.; Lapeyre‐Mestre, M.; Payrastre, B.; Beyne‐Rauzy, O.; Michel, M.; Godeau, B.; Adoue, D.; Moulis, G.; et al.
Abstract : Essentials Risk factors of bleeding in adult immune thrombocytopenia are not known. This multicenter study assessed risk factors of bleeding at immune thrombocytopenia onset. Platelet count thresholds associated with bleeding were < 20 × 10 9 L −1 and < 10 × 10 9 L −1 . Exposure to anticoagulants was a major risk factor of severe bleeding. Summary: Background: The aim of this cross‐sectional study was to assess risk factors for bleeding in immune thrombocytopenia (ITP) adults, including the determination of platelet count thresholds. Methods: We selected all newly diagnosed ITP adults included in the Cytopénies Auto‐immunes Registre Midi‐PyrénéEN (CARMEN) register and at the French referral center for autoimmune cytopenias. The frequencies of any bleeding, mucosal bleeding and severe bleeding (gastrointestinal, intracranial, or macroscopic hematuria) at ITP onset were assessed. Platelet count thresholds were assessed by the use of receiver operating characteristic curves. All potential risk factors were included in logistic regression models. Results: Among the 302 patients, the frequencies of any, mucosal and severe bleeding were 57.9%, 30.1%, and 6.6%, respectively. The best discriminant threshold of platelet count for any bleeding was 20 × 10 9 L −1 . In multivariate analysis, factors associated with any bleeding were platelet count (< 10 × 10 9 L −1 versus ≥ 20 × 10 9 L −1, odds ratio [OR] 48.2, 95% confidence interval [CI] 20.0–116.3; between 10 × 10 9 L −1 and 19 × 10 9 L −1 versus ≥ 20 × 10 9 L −1, OR 5.2, 95% CI 2.3–11.6), female sex (OR 2.6, 95% CI 1.3–5.0), and exposure to non‐steroidal anti‐inflammatory drugs (NSAIDs) (OR 4.8, 95% CI 1.1–20.7). A low platelet count was also the main risk factor for mucosal bleeding. Exposure to anticoagulant drugs was associated with severe bleeding (OR 4.3, 95% CI 1.3–14.1). Conclusions: Platelet counts of < 20 × 10 9 L −1 and < 10 × 10 9 L −1 were thresholds for major increased risks of any and mucosal bleeding. Platelet count, female sex and exposure to NSAIDs should be considered for assessment of the risk of any bleeding. Exposure to anticoagulant drugs was a major risk factor for severe bleeding.